“FROM THE CHILDREN'S FRIEND TO THE HERO OF BRAZIL: the documentary representation of Getúlio Vargas' image in new state booklets - de Oliveira, Alessandra Nunes [UNESP]; de Castro, Jetur Lima [UNESP]; dos Santos, Luiz Cezar Silva (My University, 2023)
When considering the image of Getúlio Vargas in the educational publications issued by the Department of Press and Propaganda (DIP), through a qualitative investigation based on bibliographic and documentary research, one observes the use of discursive strategies in constructing a specific representation of the political leader. In this context, the application of documentary and image analysis approaches is emphasized in examining the educational booklets titled Getúlio Vargas, the Friend of Children and Youth in the Estado Novo. These publications, aimed at children and adolescents, were used as instruments to promote civic values during the Estado Novo regime. The documentary analysis highlights the iconographic representation of Getúlio Vargas in these primers, with particular emphasis on the construction of his political figure in the context of youth and childhood during the 1940s. It underscores the pressing need for historical contextualization to gain a deeper understanding of the representational trajectories present in the documentary analysis. Finally, this study underscores the intrinsic relevance of image documentary analysis and the use of propaganda as fundamental tools for grasping the political and social dynamics during the Vargas government period. It has become evident how images played a significant role in constructing the collective imagination and guiding society towards the ideals propagated during the Estado Novo, thus consolidating the pertinence of historical research in this temporal context and the imperative of image documentary analysis in contemporary academic investigation.
“DO AMIGO DAS CRIANÇAS AO HERÓI DO BRASIL”: a representação documentária da imagem de Getúlio Vargas nas cartilhas do Estado Novo
Keywords: Discourse; Documentary Analysis; Getúlio Vargas; Image Analysis; New State-Brazil